Agricultural Development through Primary Agriculture Credit CO-Operative Societies: A Study: The Impact of Primary Agriculture Credit Co-operative Societies on Agricultural Development in Belagavi District (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Before Independence Primary Agriculture of India was backward. There was problem of finance for It. Farmers used to seek loan from the rich many lenders and businessmen these non – Institutional lenders used to occur more Interest to if there was Uncertainty of agriculture produce due to Natural calamities Farmers used to get less Income so they did not develop.There was Co-Operative movement in India after Independence. That helped the growth of Primary Agriculture Credit CO- Operative Societies. These provide financial support to the formers in rural areas the Development of Primary Agriculture Credit CO-Operative Societies. Because of Co-Operative movement on Belagavi District has leaped development of the agriculture.In Belagavi District 1422 Primary Agriculture Credit CO- Operative Societies has been functioning according to 31-3-2018 report these Primary Agriculture Credit CO- Operative Societies have 436345 farmers as their members these have lent 135608.19 corers Rupees to 344235 Farmers. With the help of this 1422 Primary Agriculture Credit CO- Operative Societies farmers have been growing food grains, pulses, commercial crops, oil seeds, horticultural crops, vegetables and fruits. Primary Agriculture Credit CO- Operative Societies has been helping to farmers to raise their income.This way Primary Agriculture Credit CO- Operative Societies have been playing very vital role in the Development of Belagavi District.